2009
DOI: 10.1056/nejmoa0808145
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation in Barrett's Esophagus with Dysplasia

Abstract: In patients with dysplastic Barrett's esophagus, radiofrequency ablation was associated with a high rate of complete eradication of both dysplasia and intestinal metaplasia and a reduced risk of disease progression. (ClinicalTrials.gov number, NCT00282672.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
1,054
9
37

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 1,304 publications
(1,140 citation statements)
references
References 25 publications
26
1,054
9
37
Order By: Relevance
“…The research work on RFA performed to date has involved a stepwise progression from initial animal studies to human studies prior to esophagectomy, human dosimetry studies, single-center studies, multicenter nonrandomized studies, and ultimately multicenter, randomized, controlled trials [1][2][3][4][5]. This process also led to modifications in the RFA technique and to the development of the focal ablation device.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The research work on RFA performed to date has involved a stepwise progression from initial animal studies to human studies prior to esophagectomy, human dosimetry studies, single-center studies, multicenter nonrandomized studies, and ultimately multicenter, randomized, controlled trials [1][2][3][4][5]. This process also led to modifications in the RFA technique and to the development of the focal ablation device.…”
mentioning
confidence: 99%
“…Studies to date, including the landmark randomized controlled trial of Shaheen et al (ablation of intestinal metaplasia [AIM] dysplasia trial), demonstrate a clear benefit for RFA in the treatment of high-grade dysplasia, ideally with endoscopic mucosal resection of any mucosal abnormalities prior to application [5,8]. In addition, preliminary results of a randomized controlled clinical trial of circumferential endoscopic mucosal resection versus focal endoscopic mucosal resection plus RFA for highgrade dysplasia and early adenocarcinoma suggest that the two techniques are comparable for the important endpoints of elimination of neoplasia and intestinal neoplasia, but the complication rate for endoscopic mucosal resection plus RFA is substantially lower [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a study by Hrobjartsson and colleagues demonstrated that non-blinded assessors were over-optimistic and “over-rated” patients in the treatment group rather than “under-rated” patients in the control group 20 . In some trials the assessment was done by people not involved in the surgery, for example blinded researchers, staff at another hospital that they were operated on at 21 , or by pathologist blinded to the treatment allocation 22 .…”
Section: Blinding Of Patients Surgeons Outcome Assessors and Caregimentioning
confidence: 99%
“…Endoscopic ablative technologies including laser or radiofrequency ablation can remove high-grade dysplasia or early cancer that was at one time only amenable to surgical treatment [18,19]. Endosocpically deployed stents for obstructing upper and lower GI cancers achieve good palliation while avoiding the potential mortality of surgical bypass.…”
Section: From Diagnostic To Therapeuticmentioning
confidence: 99%